THE LIFE OF A MAYOR IN THOMAS HARDY’S THE MAYOR OF CASTERBRIDGE - I Wayan Mulyawan (University of Muhammadiyah Purwokerto, 2013)
Literary work is fine work of art that can be easily understood by most of the people. One of the most popular works is novel. A good novel will be able to entertain the reader in such way that makes the reader keep on turning the pages. Novel is very interesting to analyze since there are no absolute rightness in exploring the meaning and message of the story. Theme is the central idea that is served implicitly in the story through the other elements such as character, plot, setting, point of view, language and style, lastly irony and symbol. Understanding the theme will make reading more joyful. The challenge in finding the theme of a novel is one point that makes the analysis of intrinsic element very interesting.